Demand for and Development of Greenery in Historic Town Squares: The Case of Zakliczyn - Kania Olga Dagmara; Hess Daniel Baldwin (Technical Transactions, 2025)
This article explores the historic development of greenery in market square spaces using the example of the Polish town of Zakliczyn in Lesser Poland. Contemporary Polish conservation policy aimed at preserving a public space’s historic values is often at odds with the needs and demands of the general public, whose members appear to be in consensus that urban public spaces, especially market squares, should feature more greenery. This study traces the spatial development of Zakliczyn’s market square throughout the last 150 years based on historic cartography and iconography, as well as contemporary orthophotomaps, and demonstrates that greenery in this historic market square is indeed a relatively recent phenomenon, although scant fragments of it did appear as early as immediately before World War II. It also contrasts the greenery in market squares from the People’s Republic of Poland period (1947 to 1989) with the most recent revitalizations occurring during the past 5 years.